2014
DOI: 10.1002/sia.5502
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interface investigation of electrochemically induced corrosion on a quaternary bronze

Abstract: A quaternary (Cu‐Zn‐Sn‐Pb) cast bronze was submitted to an electrochemical corrosion experiment using an anodic polarization sweep. The surface/interface chemical analysis of the patina removed after the anodic polarization and the metallographic observations on the corroded bulk alloy highlight the onset of a dezincification process followed by a decuprification process, as well as the formation of a Sn‐enriched layer located at the interface patina‐bulk alloy. Different local corrosion patterns, as CuCl prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The changes in the composition of the bronze base layer revealed that the Cu and Zn contents decreased, whereas the Sn and Pb contents relatively increased. These results are in line with the corrosion mechanisms of Cu-Zn-Sn-Pb and Cu-Zn-Sn alloys and the findings of previous studies [20,30,31,[37][38][39].…”
Section: Correlation Between Composition and Corrosion Products Of Su...supporting
confidence: 92%
See 1 more Smart Citation
“…The changes in the composition of the bronze base layer revealed that the Cu and Zn contents decreased, whereas the Sn and Pb contents relatively increased. These results are in line with the corrosion mechanisms of Cu-Zn-Sn-Pb and Cu-Zn-Sn alloys and the findings of previous studies [20,30,31,[37][38][39].…”
Section: Correlation Between Composition and Corrosion Products Of Su...supporting
confidence: 92%
“…Several studies conducted under outdoor environmental conditions revealed that cuprite and cassiterite are mixed in the reddish-brown patina formed on top of the base metal. At S50 (2400 h), the artificial patina comprised cuprite (Cu: 79.33-84.38 wt%, Sn: 0.33-0.92 wt%), cassiterite (Cu: 55.71 wt%, Sn: 6.07 wt%), and a mixed layer of cassiterite and cu- The decrease in Cu and Zn is respectively attributable to the selective dissolution of Cu and Zn ions owing to the decuprification and dezincification processes within bronze; the cation moves toward the boundary through the patina inside the alloy, and the anion moves toward the inside of the alloy [37,39,40]. In particular, the initial corrosion is mainly (>90%) caused by Cu and Zn [31,38]; Sn forms a patina layer upon condensing as it is an insoluble corrosion product and is known to stabilize the patina through passivation [30,41].…”
Section: Corrosion Mechanism Of Sulfide Patinamentioning
confidence: 99%
“…[37][38][39] However, these methods have problems in attaining uniform brochantite structures on the copper surface and the artificially induced patinas tend to show poor adhesion so that post-process treatments are sometimes required for improving adhesion of the patina to the metal surface. 40,41 As a result, the application of patina has been limited despite its advantages. Therefore, it is necessary to develop a new strategy for achieving uniform and robust brochantite rapidly as a sustainable corrosion-resistant material even in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…At 0.5 mVs −1 the greatest protective layer is formed. Peak A 1 is related to the deposition of Cu + and Cu 2+ species, [ 35 ] leading mainly to the formation of Cu 2 O, while peak A 2 is associated with the formation of CuO or Cu(OH) 2 . However, the development of the anodic peak A' 1 at 5 and 7 mVs −1 is associated with the existence of an absorbed layer of (CuCl) ads .…”
Section: Resultsmentioning
confidence: 99%